2014
DOI: 10.1021/pr401202d
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Brain Proteome in Alzheimer’s Disease Using Multiplexed Mass Spectrometry

Abstract: We have compared the brain proteome in the temporal neocortex between Alzheimer's disease (AD) patients and non-AD individuals by using shotgun mass spectrometry based on a stable isotope dimethyl labeling. A total of 827 unique proteins were identified and quantitated. Of these, 227 proteins were found in at least 9 out of 10 AD/control pairs and were further subjected to statistical analysis. A total of 69 proteins showed different levels (p-value < 0.05) in AD versus control brain samples. Of these proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 89 publications
(176 reference statements)
11
76
3
Order By: Relevance
“…However, modern scientific approaches help in gathering as much information on the disorder as possible. Those methods are mainly proteomics methods [98][99][100][101][102] but also include metabolomics [103][104][105][106] and transcriptomics [107]. The ideal biomarker for AD should detect a fundamental feature of neuropathology and be validated in neuropathologically confirmed cases.…”
Section: Dementiamentioning
confidence: 99%
“…However, modern scientific approaches help in gathering as much information on the disorder as possible. Those methods are mainly proteomics methods [98][99][100][101][102] but also include metabolomics [103][104][105][106] and transcriptomics [107]. The ideal biomarker for AD should detect a fundamental feature of neuropathology and be validated in neuropathologically confirmed cases.…”
Section: Dementiamentioning
confidence: 99%
“…Importantly, the degree of synaptic loss shows a close correlation with the degree of dementia (Coleman and Yao, 2003). It has been previously shown that the protein levels of different septins are altered in the temporal neocortex of Alzheimer's disease patients as compared to non-Alzheimer's disease subjects (Hanai et al, 2004;Musunuri et al, 2014), suggesting that septins could represent early markers linked to synaptic dysfunction and synaptotoxicity. Consistent with this idea, presynaptically enriched SEPT8 controls the formation of the soluble N-ethylmaleimidesensitive factor attachment protein receptor (SNARE) complex and the subsequent docking of synaptic vesicles to the presynaptic membrane (Ito et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…Initially, proteins are enzymatically digested to peptides and then labeled with isobaric tags at the free amino-termini and epsilon-amino groups of lysine residues. The isobaric tags contain a reactive group for peptide binding, a balancer group, a cleavage site proteome studies were performed in our group using DML to analyze patients with AD [9] and ALS [65].…”
Section: Chemical Labeling Methodsmentioning
confidence: 99%
“…stable isotope labeling or label free method, and can be easily used for large-scale proteomic experiments. In our recent study [9], by employing a stable isotope DML MS approach we identified 827 brain proteins, 69 of which were significantly changed in AD compared non-neurological control brains. A quantitative proteomic strategy based on the cloud-point extraction method for the separation and enrichment of hydrophobic MPs in combination with DML MS analysis was also employed by our group [17] to quantitatively identify protein expression changes in AD temporal neocortex samples.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation